Trends in pharmaceutical expenditure in the Taiwan National Health Insurance database at different hospital levels - Ching-Hu Chung (Becaris Publishing Limited, 2022)
Aim: This study aimed to understand themedication usage among different hospitals in Taiwan. Materials & methods: The NHI claims database consisting of claims prescription drugs in Taiwan was used to determine drug prescriptions in different hospitals. Results: In the medical center, L01X showed the highest drug expenditure and the drug prescription pattern in regional hospitals was similar to that in the medical center. The highest drug expenditure in the district hospital and clinics was A10B. Conclusion: Our analysis suggests that the annual pharmaceutical expenditures from 2016 to 2018 were increasing over time in all hospitals. The generic drug usage in medical centers/regional hospitals was lower than district hospitals/clinics.